What is the gap in activity and participation between people with disability and the general population in Taiwan? - Tzu-Ying Chiu; Chia-Feng Yen; Reuben Escorpizo; Wen-Chou Chi; Tsan-Hon Liou; Hua-Fang Liao; Cheng-Hsiu Chou; Wen-Hui Fang (BMC, 2017)
Abstract Background In 2010, the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) was developed, based on the concept of the International Classification of Functioning, Disability and Health (ICF). The ICF provides a common language and framework for health and health-related status and attempts to integrate the biopsychosocial model as a multidimensional perspective in understanding functioning. Activities and participation (AP) is one salient component of the ICF refers to the execution of a task by an individual, and how such tasks are involved in their daily life. It is essential to examine the gap between the general adult population and adults with disabilities. This gap may be attributed to health status, personal factors, and natural and social environments, which include social and health services and policies. The purposes: (1) To develop a normative activity and participation (AP) value for the adult population and people with disabilities; and (2) to compare the gap in AP normative values between the two groups in Taiwan. Methods We use the WHODAS 2.0 to survey and develop a normative AP value for the general adult population, and used secondary data from National Disability Eligibility Determination System (NDEDS) of Taiwan to describe the AP functioning distribution of adult with disability. There were 1100 participants, selected by stratified proportional sampling from two cities. There were also 144,850 participants who were adults with disability, selected from the secondary database in Taiwan. Results and conclusions The AP curve for the disabled population increased rapidly at the beginning. The summary score was 13.21 in the performance at 90 percentile for the general population and 82.61 score for disabled adults that the similar gap in every domain, its means that there are significant functioning difference and health equality in general adults population and adults with disabilities. This presents a substantial challenge for both the government and the whole population of Taiwan, to begin considering how to reduce the gap in AP functioning and promote equality for people with disabilities, using social welfare policy. It is important to make sure disabled people have the same rights to be included in society as anybody else and better access to things in all areas of life that are according to Convention on the Rights of Persons with Disabilities (CRPD).